1977
DOI: 10.1099/00221287-101-1-163
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and Ultraviolet-induced Mutation in Escherichia coli: Interaction Between Plasmid and tif-1 Mutator Effects

Abstract: I N T R O D U C T I O NCertain plasmids increase ultraviolet (u.v.) resistance and spontaneous and u .v. mutagenesis in Salmonella typhimurium (Howarth, I 966; MacPhee, 1973 ;Mortelmans & Stocker, 1976). In Escherichia coli, thermally-induced expression of the tif-I mutation similarly causes enhancement of spontaneous and u.v.-induced mutagenesis (Witkin, I 974). The effects of both plasmid expression (MacPhee, 1973 ;Monti-Bragadin, Babudri & Samer, 1976) and tif-I expression (Castellazzi, George & Buttin, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…A sequence with homology to known LexAbinding sequences is located upstream of the mucAB operon (Table 3). The inducibility of the mucAB locus is consistent with the ability of pKM101 to enhance (354,356) and with the synergistic interactions that have been observed between pKM101 and the recA441 mutation (50,79,354). It has been suggested that R46, the parent of pKM101, codes for an element which negatively regulates the expression of the muc genes (81).…”
Section: Colisupporting
confidence: 75%
“…A sequence with homology to known LexAbinding sequences is located upstream of the mucAB operon (Table 3). The inducibility of the mucAB locus is consistent with the ability of pKM101 to enhance (354,356) and with the synergistic interactions that have been observed between pKM101 and the recA441 mutation (50,79,354). It has been suggested that R46, the parent of pKM101, codes for an element which negatively regulates the expression of the muc genes (81).…”
Section: Colisupporting
confidence: 75%
“…Observations such as the enhancement of Weigle reactivation by pKM101 (24) and the synergistic effects of plasmid pKM101 and recA441 (tif-1) mutations (6,8,32) have indicated that at least some of the effects of pKM101 on mutagenesis and recovery from DNA damage are inducible. In the work described in this paper, we have shown that this inducibility is due, at least in part, to the induction of the mucA and mucB gene products.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that plasmids pKM101 and R46 are unable to enhance mutagenesis or increase resistance to UV killing in a recA or lexA(Ind-) background (32) suggested that the muc genes of pKM101 might be part of the recA+ lexA+ regulatory network. Furthermore, certain observations, such as the enhancement of Weigle reactivation by pKM101 (33) and the synergistic effects of pKM101 and recA441 (tif-1) mutations (6,8,32), had indicated that some of the pKM101-mediated effects were inducible. However, these physiological experiments did not distinguish between the possibility that a plasmid-encoded gene was induced and the possibility that the plasmid-mediated process required INDUCTION OF muc GENES 1307 the induction of a chromosomally encoded gene but not the induction of a plasmid-encoded gene.…”
mentioning
confidence: 99%
“…This type of plasmid-host interaction has not been observed previously. Other plids have been shown to enhance the expression of SOS mutagenesis and repair functions in recA+ (24,27,39), as well as in tif-strains (8,39). In all cases, the molecular mechanism underlying the interaction has remained obscure.…”
Section: Discussionmentioning
confidence: 99%